The Importance of Teaching Phonological-Based Spelling Skills. (Kairaranga, 2014)
In a recent study we (Greaney & Arrow, 2009) undertook an analysis of the types of spelling errors that students had made during a National Education Monitoring Project writing task (Crooks, Flockton & White, 2007). We discussed several issues related to spelling, including the value of analysing students’ error-response patterns as a way of identifying some of the likely causes for these errors. As Bissaker and Westwood (2006) note “A pattern of errors (miscues) can indicate children’s grasp of regular grapho- phonic relationships and their awareness of less predictable letter sequences” (p. 25). In the current paper the relevance of analysing spelling error- responses as a source of data from which to design further explicit spelling instruction is discussed. Some possible teaching activities that may be used with either small groups or whole classes that aim to develop (in students) a more in-depth orthographic knowledge of words are also presented.